On the performance of blanking nonlinearity in real-valued OFDM-based PLC - Juwono, Filbert Hilman; Guo, Q.; Huang, D.; Chen, Y.; Xu, L.; Wong, K. (The Institute of Electrical and Electronics Engineers, Inc, 2018)
© 2016 IEEE. To mitigate the impulsive noise in orthogonal frequency-division multiplexing (OFDM)-based power-line communications (PLC), a blanker can be employed at the receiver. In the literature, the performance of the blanker has been discussed and analyzed thoroughly. However, the analysis was limited only to passband OFDM PLC systems with complex-valued baseband representation. This paper aims to derive a mathematical expression of the output signal-to-noise ratio (SNR) of a blanker in baseband OFDM-based PLC, which are real-valued and used in some PLC standards. We also analyze the performance of separate real/imaginary blanking, instead of the traditional amplitude blanking, in passband OFDM-based PLC systems. It will be shown that the performance of amplitude blanking is similar to separate real/imaginary blanking in high signal-to-impulsivenoise ratio (SINR) values. However, when the SINR is low, the performance of amplitude blanking is better than the separate real/imaginary blanking. The difference is about 1 dB for SINR = -10 dB and 1.5 dB for SINR = -30 dB when signalto- background-noise ratio, SBNR = 25 dB and impulsive noise probability p = 0.01.